CONFERENCE BOOK : 45 YEARS HIGHER EDUCATION IN THE AREA OF SECURITY – EDUCATIONAL CHALLENGES AND SECURITY PERSPECTIVES, - Chupeska, Ana (University “St. Kliment Ohridski”- Bitola & Faculty of Security- Skopje, 2022)
This article will reflect on specific form of populist pollical mobilsation, and that is ethno- populism (in line with Janne, Stavrikasis, Mudde) firstly, via addressing its triggers such as prolonged crises initiated by recent pandemic with covid 19 and Russian invasion over Ukraine. Secondly, both global distortions have raised a question of ethno-populist movements around the globe, for which there are many prominent examples that can serve to demonstrate the case in point : from Donald Trump naming the “China virus”, to Putin’s preoccupation with denazification, as well as many other nationalist acters that have taken an ethno-populist form. Consequently, I will discuss the ethno-populist glare in case of North Macedonia possible security related risks.
FROM ETHNOPOPULISM TO SECURITY RISKS
Keywords: crises, etnhnopopuslim, security risks, North Macedonia